ANALISIS PEMAHAMAN GURU MI TENTANG ALAM SEMESTA MELUAS DALAM PERSPEKTIF ISLAM DAN SAINS - Yayuk Cicilia; Rian Vebrianto; Zarkasih Zarkasih (Universitas Pahlawan Tuanku Tambusai, 2020)
Some MI teachers do not understand about the expanding universe in Islamic and scientific perspectives. So the authors are interested in raising the analysis of this problem. The aim of the study was to find out the understanding of teachers and prospective MI teachers in the field of science studies about the expanding universe in Islamic and scientific perspectives. The type of this research is survey research. Which research phase used is quantitative descriptive. Analysis of the data is to calcify data, test hypotheses, analyze findings and make conclusions. Based on the results of the questionnaire it was found that the teacher's understanding of the universe expanded in Islamic perspective and science were in the category of understanding.